Avaliação da qualidade da água e autodepuração do ribeirão do meio, Leme (SP) - de Souza Sardinha, Diego [UNESP]; Tomazini da Conceicao, Fabiano [UNESP]; Goncalves de Souza, Antonio Donizetti; Silveira, Alexandre; de Julio, Marcelo; de Souza Inacio Goncalves, Julio Cesar (Assoc Brasileira Engenharia Sanitaria Ambiental, 2008)
This investigation utilized hydrochemical relations to evaluate possible anthropogenic inputs at Meio Stream, São Paulo State. Realized three sampling of water during the months of February, April and July/2005, in five sampling points analyzing: discharge, temperature, turbidity, pH, electrical conductivity (EC), dissolved oxygen ( DO), TDS (total dissolved solids), TSS (total suspended solids), Ca(2+), Mg(2+), Na(+), K(+), HCO(3)(-), Cl(-), SO(4)(2-), PO(4)(3-) and NO(3)(-). The characteristics of water close to spring until Leme city allow concluding that there is a small interference in its quality, however the absence of treatment of domestic wastewater at Leme city reduced its quality. It was applied the QUAL 2K modeling to evaluate the Meio Stream auto-purification identified the auto-purification zones and indicated the necessity of secondary wastewater treatment, with 76% of efficiency.

Este trabalho utilizou relações hidroquímicas para avaliar possíveis entradas antropogênicas nas águas superficiais do Ribeirão do Meio (SP). Realizaram-se três coletas de água durante os meses de fevereiro, abril e julho de 2005 em cinco pontos de coleta analisando: vazão, temperatura, turbidez, pH, condutividade, oxigênio dissolvido, sólidos totais dissolvidos, sólidos totais em suspensão, Ca2+, Mg2+, Na+, K+, HCO3-, Cl-, SO42-, PO43- e NO3-. As características da água próximo à nascente até a cidade de Leme permitem concluir que há pouca interferência na sua qualidade, porém, a falta de tratamento para o esgoto doméstico da cidade de Leme piora a sua qualidade. Para se modelar à autodepuração utilizou-se o modelo QUAL 2K, que identificou as zonas de autodepuração e indicou a necessidade de tratamento de esgotos em nível secundário, com eficiência de 76%.
Evaluation of the water quality and auto-purification from the meio stream, Leme (SP)
Keywords: Water quality; anthropogenic influences; auto-purification mathematical modeling; environmental management